2018
DOI: 10.1242/jcs.211631
|View full text |Cite
|
Sign up to set email alerts
|

TFIIH localization is highly dynamic during zygotic genome activation in Drosophila, and its depletion causes catastrophic mitosis

Abstract: In , zygotic genome activation occurs in pre-blastoderm embryos during rapid mitotic divisions. How the transcription machinery is coordinated to achieve this goal in a very brief time span is still poorly understood. Transcription factor II H (TFIIH) is fundamental for transcription initiation by RNA polymerase II (RNAPII). Herein, we show the dynamics of TFIIH at the onset of transcription in embryos. TFIIH shows an oscillatory behaviour between the nucleus and cytoplasm. TFIIH foci are observed from interph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 62 publications
(89 reference statements)
1
14
0
Order By: Relevance
“…However, we detected that many transcripts were downregulated and many others were upregulated. These results correlate with our data in Drosophila, in which both up- and downregulated transcripts were observed in p8 and p52 mutant organisms [ 37 , 38 ]. Interestingly, the increase in the levels of several specific genes in response to TPL also occurred in other breast cancer cell lines.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, we detected that many transcripts were downregulated and many others were upregulated. These results correlate with our data in Drosophila, in which both up- and downregulated transcripts were observed in p8 and p52 mutant organisms [ 37 , 38 ]. Interestingly, the increase in the levels of several specific genes in response to TPL also occurred in other breast cancer cell lines.…”
Section: Discussionsupporting
confidence: 92%
“…While analysing the transcriptome of TFIIH mutants in Drosophila , we previously reported that not all genes responded equally and that the transcript levels of numerous genes increase in TFIIH mutant tissues [ 37 , 38 ]. Therefore, to explore whether TPL also generates a differential effect on gene expression in TAM and NT cells, we analysed the transcriptomes of these cells after incubation with 125 nM TPL for 4 h, a concentration found to reduce equally RNAPII levels by half in NT and TAM cells, to affect mildly cell viability ( figure 3 a,b ).…”
Section: Resultsmentioning
confidence: 99%
“…This phosphorylation is one of the essential conditions for the activation of the kinase [23][24][25]47,48]. In Drosophila, the CAK made of Cyclin H and CDK7 is also localized in the nucleus in early embryos [49]. In the Nup62-depleted premeiotic spermatocytes, this phosphorylation occurred, as observed in control cells.…”
Section: Selective Nuclear Export Of Cycb Essential For the Cdk Fullmentioning
confidence: 83%
“…These proteins are enriched around the metaphase chromosomes and in some cases (e.g., p52) they appear to concentrate in a region corresponding to the spindle [113]. Moreover, in embryos from p8 and hay mutant mothers or Cdk7 RNAi mothers, most spindles are morphologically aberrant and show abnormal chromosome segregation [113]. Drosophila Xpd is required for proper spindle dynamics and chromosome segregation in early embryos.…”
Section: Mitotic and Meiotic Roles Of The Tfiih Complex Componentsmentioning
confidence: 99%
“…Studies using fluorescently tagged TFIIH components have shown that Hay, p8, p52, and Cdk7 exhibit similar localization patterns in live early embryos. These proteins are enriched around the metaphase chromosomes and in some cases (e.g., p52) they appear to concentrate in a region corresponding to the spindle [113]. Moreover, in embryos from p8 and hay mutant mothers or Cdk7 RNAi mothers, most spindles are morphologically aberrant and show abnormal chromosome segregation [113].…”
Section: Mitotic and Meiotic Roles Of The Tfiih Complex Componentsmentioning
confidence: 99%